Teores de sódio em rações com relação cátion-aniônica constante para poedeiras comerciais leves - Cañas Mendoza, Edwin Alberto (2015)
The objective in this study was to evaluate the different sodium content effect with constantly cation-anion ratio on performance and egg quality of light laying hens in post-peak production under natural conditions of heat stress in summer. Five hundred seventy six laying hens Hy-Line in post-peak production distributed in a completely randomized design were used, consisting of five treatments with increasing sodium levels, as follows: 0.10; 0.14; 0.18; 0.22; 0.26%, while maintaining constantly cation-anion ratio (Na+K) /Cl of 4.0, plus a control treatment with sodium recommended by lineage. The experiment lasted 84 days divided into 4 periods of 21 days each. Egg production, feed intake, egg mass, feed conversion, egg weight, specific weight, shell weight, shell thickness and Haugh units were the characteristics evaluated. Sodium levels had no effect on consumption, egg weight, egg specific weight and shell weight per unit surface area. However, such levels had a quadratic effect production, conversion, Haugh units and shell weight in periods 2 and 3. In this cycle, sodium requirements were estimated at 0.20; 0.20; 0.21; 0.21%, respectively. Considering the estimates, the electrolyte balance and different levels of sodium had no effect on performance and egg quality, when maintaining the cation-anion ratio in four.